2020
DOI: 10.1186/s12882-019-1675-5
|View full text |Cite
|
Sign up to set email alerts
|

C1GALT1 expression is associated with galactosylation of IgA1 in peripheral B lymphocyte in immunoglobulin a nephropathy

Abstract: Background: More and more studies demonstrated that genetic variation at C1GALT1 influences Gd-IgA1 level in IgAN. However, whether the expression of β1, 3-galactosyltransferase (β1, 3Gal-T) was influenced may provide insights into how Gd-IgA1 levels are controlled in IgAN. Methods: Thirty IgAN patients diagnosed in Tianjin Medical University General Hospital from April to September 2018 and 30 healthy volunteers whose age and gender matched with patients were enrolled in this study. Total Gd-IgA1 levels in pl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Kiryluk et al ( 57 ) used in vitro small interfering (si)RNA knockdown to demonstrate that C1GALT1 can determine the secretion rate of Gd-IgA1 in serum IgA1-producing cells. Xing et al ( 58 ) discovered that C1GALT1 expression in peripheral B lymphocytes of patients with IgAN has a negative correlation with increased Gd-IgA1 levels and is markedly downregulated compared with the increase of Gd-IgA1 level. The aforementioned study involved 30 patients with IgAN and 30 healthy volunteers in China ( 58 ).…”
Section: C1galt1 In Normal Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Kiryluk et al ( 57 ) used in vitro small interfering (si)RNA knockdown to demonstrate that C1GALT1 can determine the secretion rate of Gd-IgA1 in serum IgA1-producing cells. Xing et al ( 58 ) discovered that C1GALT1 expression in peripheral B lymphocytes of patients with IgAN has a negative correlation with increased Gd-IgA1 levels and is markedly downregulated compared with the increase of Gd-IgA1 level. The aforementioned study involved 30 patients with IgAN and 30 healthy volunteers in China ( 58 ).…”
Section: C1galt1 In Normal Developmentmentioning
confidence: 99%
“…Xing et al ( 58 ) discovered that C1GALT1 expression in peripheral B lymphocytes of patients with IgAN has a negative correlation with increased Gd-IgA1 levels and is markedly downregulated compared with the increase of Gd-IgA1 level. The aforementioned study involved 30 patients with IgAN and 30 healthy volunteers in China ( 58 ). Gd-IgA1 level was measured by an enzyme-linked immunosorbent assay, and the results revealed that Gd-IgA1 levels ranged between 8.55 and 14.48 U/ml in patients with IgAN and between 3.97 and 12.15 U/ml in healthy controls ( 58 ).…”
Section: C1galt1 In Normal Developmentmentioning
confidence: 99%
See 3 more Smart Citations